a Arab: Depression and its Relationship with the Five Basic Human Needs in the Novel Wiṣāl Al-Rūh by Sarah Jawhar (Literary Psychological Studies) - Buana, Cahya; Hasanah, Uswatun (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2025)
يهدف هذا البحث إلى معرفة أشكال الاكتئاب التي عانت منها الشخصية الرئيسية في رواية